Shaped by use. Urban space appropriation in Macau - Soares, Nuno (Morfologia Urbana nos Países Lusófonos. Actas da Conferência Internacional, 2012)
The contemporary city is a complex system where a multitude of factors and dwellers interact, creating a multi-layered spatial structure that supports the urban life. To successfully research and intervene in this context, one needs to develop fitting approaches and methods to be able to analyze it in depth.
Accepted: 2012-06-25T17:03:41Z